Exploring the feasibility of technological transfers of two by-catch reduction devices in the crustacean bottom trawling of the central Mediterranean - Geraci, Michele Luca; Sardo, Giacomo; Scannella, Danilo; Falsone, Fabio; Di Maio, Federico; Gancitano, Vita; Fiorentino, Fabio; Chirco, Pierangela; Massi, Daniela; Vitale, Sergio (Frontiers in Marine Science, 2023)
Introduction Most Mediterranean fish stocks are overexploited owing to high fishing efforts and poor exploitation patterns. Demersal trawl fisheries are considered the most impactful fishery type because of the high quantities of unwanted catch that is then routinely discarded at sea. Methods In the present study, two types of by-catch reduction devices (BRDs), that is a sorting grid (Grid-T45 40 mm) and a T90 50 mm codend, were compared to a typical commercial bottom trawl net (control) in terms of size structures and catch per unit effort to assess the effect of gear modification on the selectivity of crustacean fisheries in the central Mediterranean Sea. In particular, three randomly selected trawlers were involved in a paired hauls experiment fishing at the same time in the same fishing ground. Each trawler carried out four hauls per day during a 3-day campaign for a total of 36 hauls. The target species of the fishery is Parapenaeus longirostris (herein DPS), and the main commercial by-catch is Merluccius merluccius (herein HKE). Results The results showed that the landing per unit effort (LPUE) of DPS was higher for Grid-T45 40 mm net, although it did not differ significantly from that of the control net. Conversely, the discard per unit effort (DPUE) of the control net was significantly higher than of both BRD configurations. For HKE, a slightly higher LPUE was recorded using the T90 50 mm codend compared to that of the control, but this result was not statistically significant. The lowest DPUE was found for the T90 50 mm codend, with significant differences compared to that of the control and Grid-T45 40 mm net. The catch comparison of the size structures analysed through generalised linear mixed models highlighted that the Grid-T45 40 mm net was more effective in catching adult DPS, whereas the T90 50 mm codend was more selective for adult HKE. Discussion In conclusion, although further studies should be carried out in future to test the performance of the BRDs in different areas and seasons, the investigated gear seems to be promising for reducing the catch of undersized individuals and contributing to mitigating the current overfishing of DPS and HKE.